How long do we keep up with the Joneses? Herding time horizons in the dry bulk shipping markets - Nektarios Michail; Konstantinos D. Melas (Asian Journal of Shipping and Logistics (AJSL), 2021)
We estimate intentional and unintentional herding in the dry-bulk, ocean-going segment that spans from August 1998 to January 2020 and measure how this can impact vessel orders. As the results suggest, while intentional herding has a large effect on the orders of the newbuilding vessels, the impact is very short-lived. On the contrary, unintentional herding, related to common environmental factors, has a smoother but more time persistent effect on the newbuilding vessels. The findings suggest that the key players in the market do not only affect the dry-bulk market with their decisions but also the logistics trade and ultimately the world economy. Thus, the inclusion of the dry bulk key shipowners by the policymakers in the discussions before reaching an important decision could minimise the volatility of the overall sector.
Keywords: 650; Dry bulk; Herding behavior; Impulse responses; Shipping markets